Correlates of hospital use in homeless and unstably housed women: the role of physical health and pain. - Doran, Kelly M; Shumway, Martha; Hoff, Rani A; Blackstock, Oni J; Dilworth, Samantha E; Riley, Elise D (Women's health issues : official publication of the Jacobs Institute of Women's Health, 2014)
To examine correlates of emergency department (ED) use and hospitalizations in a community-based cohort of homeless and unstably housed women, with a focus on the role of physical health and pain.
Keywords: Adult; Cross-Sectional Studies; Emergency Service, Hospital; Female; Health Status; Homeless Persons; Hospitalization; Housing; Humans; Pain; Regression Analysis; San Francisco; Socioeconomic Factors